Acquired Immunodeficiency Syndrome Patient with A Dengue Hemorrhagic Fever Co-Infection - Dedy Hadi Prawono; Bramantono (Indian Journal of Forensic Medicine & Toxicology, 2021)
Infection of human immunodeficiency virus (HIV) is the most infectious disease in tropic disease infection and co-infection of HIV is very large, one of which is DHF. Research on DENV-HIV is still limited. A patient 29-year-old, referred to Dr. Soetomo Hospital with chief complain nausea from yesterday. Accompanied epigastric pain, stomach feel full and decreased of appetite. Laboratory test finding Hb 18,6 g/dL, leukosit 2910/mm3, trombosit 9000/mm3, HCT 51,5 %, Anti dengue IgG 29,9 and IgM 10,5 on 2nd day admission, Anti dengue IgG 14,3 and IgM 13,1 on two weeks from out of admission. The most common symptom in HIV patients with co-infection DHF is fever and loss of appetite. Patients with DENV-HIV have plasma leakage. Patient with DENV-HIV found an increase in eosinophil and pulse but found a lower increase in serum hematocrit compared with DENV patients, but lower hematocrit levels in this patients can be caused in patients using zidovudine, which is associated with anemia caused by zidovudin side effects.